Uncovering the molecular mechanisms of Qingdu Zengye Decoction in the treatment of nasopharyngeal carcinoma: an integrative investigation - Quan, Qi; Liu, Zeyu; Ding, Ran; Lin, Yongmiao; Zhang, Sihe; Luo, Wei; Lei, Mengjie; Fan, Teng; Su, Xin; Huang, Yuanyuan; Peng, Roujun; Zhang, Bei (Frontiers in Pharmacology, 2025)
BackgroundNasopharyngeal carcinoma (NPC) remains a therapeutic challenge due to its aggressive nature and limited treatment efficacy. Traditional Chinese Medicine, particularly Qingdu Zengye Decoction (QZD), has shown clinical potential, but its mechanistic basis in NPC treatment requires elucidation.PurposeThis study aims to elucidate the mechanisms of action of QZD in the treatment of NPC, focusing on its multi-target regulatory effects on cell apoptosis, oncogenic signaling pathways, and tumor immune microenvironment.MethodsAn integrative approach combining computational pharmacology, functional experiments, and single-cell transcriptomic profiling was employed to dissect QZD’s anti-NPC mechanisms. Network pharmacology and protein-protein interaction (PPI) analysis was used to identify potential QZD targets. Functional assays (cell proliferation, apoptosis, colony formation) and Western blotting were used to validate key pathways. Molecular docking was applied to assessed ligand-target binding affinities. Single-cell RNA sequencing (scRNA-seq) was used to analyzed spatial expression patterns in NPC tumor samples.ResultsQZD suppressed tumor progression by inducing apoptosis through modulating Bax in a dose-dependent manner and inhibiting the PI3K-Akt signaling pathway. Network pharmacology analysis identified AKT1, MTOR, HIF1A, SRC, and ESR1 as core regulatory genes. scRNA-seq revealed compartment-specific target localization: AKT1/ESR1 in tumor cells, SRC/IL6 in myeloid cells, and MTOR/HIF1A across stromal compartments. Molecular docking confirmed strong interactions between QZD compounds (e.g., quercetin, luteolin) and these targets. Upregulation of IL6 was observed and its dual immune-modulatory effects involving tumor suppression and microenvironment reprogramming was suggested.ConclusionQZD exerts anti-tumor effects in NPC through apoptosis induction, PI3K-Akt pathway suppression, and multi-compartmental tumor microenvironment modulation. Its ability to concurrently target oncogenic signaling and immune regulation positions QZD as a promising therapeutic strategy for advanced NPC.